Phosphate positive electrode material and preparation method thereof, positive electrode plate and secondary battery
By covering the high-crystalline carbon layer on the core surface of the sodium fluorine vanadium phosphate of the phosphate positive electrode material, the problem of poor electron conductivity of traditional phosphate positive electrode materials is solved, and the specific capacity, rate performance and circulation performance of the secondary battery are improved, and a high energy density battery is obtained.
Patent Information
- Application Number
- CN202411846650.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
The electron conductivity of traditional phosphate positive electrode materials is poor, which makes it difficult to improve its discharge capacity and rate performance in secondary batteries.
By covering the surface of the sodium vanadium fluorophosphate material with high crystallinity, the electron conductivity and structural stability of the phosphate positive electrode material are improved, and its compaction density and BET specific surface area are improved.
The specific capacity, rate performance and cycling performance of phosphate positive electrode materials in secondary batteries are significantly improved, thereby obtaining a high-energy density secondary battery.
Smart Images

Figure CN119764376A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art
[0002] Sodium-ion Battery (SIB) is a kind of battery that relies on sodium ions (Na + ) is a secondary battery that moves between the positive and negative electrodes to achieve charge and discharge. Its working principle is similar to that of the mainstream secondary battery lithium-ion battery (LIB). It has attracted much attention due to its advantages such as abundant sodium ion resources in the earth's crust and low price, and has become the most likely substitute for LIB in grid-scale energy storage. Among the positive electrode materials of sodium-ion batteries, polyanionic compounds (PAC) have very excellent cycle life and have very broad application prospects in the field of SIB.
[0003] Sodium Super Ionic Conductor (NASICON) is one of the representative PAC materials. It has a stable three-dimensional open framework and can realize Na + Phosphate materials, such as sodium vanadium phosphate (Na3V2(PO4)3, NVP) and sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF), are typical NASICON materials and can be used as positive electrode materials for SIBs. However, the poor electronic conductivity of traditional phosphate positive electrode materials makes it difficult to improve the discharge capacity and rate performance of secondary batteries prepared using traditional phosphate positive electrode materials. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery, aiming to solve the technical problem of poor electronic conductivity of traditional phosphate positive electrode materials.
[0005] In a first aspect, an embodiment of the present application provides a phosphate positive electrode material, the phosphate positive electrode material comprising a core and a carbon layer coating the core;
[0006] The inner core includes sodium vanadium fluorophosphate material;
[0007] The compaction density of phosphate cathode material is ≥1.78g / cm 3 , BET specific surface area ≥9m 2 / g;
[0008] The Raman spectrum of the phosphate positive electrode material has a D peak and a G peak, and the intensity ratio of the D peak to the G peak is (1.03-1.05):1.
[0009] In the technical solution of the embodiment of the present application, the phosphate positive electrode material has a sodium vanadium fluorophosphate material with a high working voltage as the core, and is coated with a carbon layer with high crystallinity on the core, which not only gives it better electronic conductivity and structural stability, but also improves its compaction density and BET specific surface area, which is beneficial to improve the specific capacity and rate performance of the secondary battery prepared using the phosphate positive electrode material, and thus obtain a secondary battery with high energy density.
[0010] In some embodiments, the mass ratio of the inner core to the carbon layer is 100:(1.75-3.3).
[0011] In this embodiment, by controlling the mass ratio of the core and the carbon layer, higher electronic conductivity can be achieved to improve the specific capacity, rate performance and cycle performance of the material. If the mass ratio of the carbon layer is too low, an effective coating structure and conductive network cannot be formed, and the effect of improving electronic conductivity is not ideal; if the mass ratio of the carbon layer is too high, the content of electrochemically active substances will be reduced, the material resistance will be increased, and the Na + diffusion, thereby reducing the comprehensive electrochemical performance of the prepared phosphate cathode material.
[0012] In some embodiments, the carbon layer has a thickness of 1 nm to 3 nm.
[0013] In this embodiment, controlling the thickness of the carbon layer within a suitable range can improve electronic conductivity, enhance structural stability, and inhibit side reactions, thereby improving the specific capacity, rate performance, and cycle performance of the prepared phosphate positive electrode material.
[0014] In some embodiments, the D50 particle size of the phosphate positive electrode material is 4 μm to 10 μm.
[0015] In this embodiment, the phosphate positive electrode material has a suitable particle size to ensure that Na + It can be embedded and released relatively quickly, improving the specific capacity and rate performance of the secondary battery, and is easily dispersed in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the consistency and stability of the positive electrode sheet prepared using phosphate positive electrode materials.
[0016] In a second aspect, the present application provides a method for preparing a phosphate positive electrode material, comprising the following steps:
[0017] Mixing a vanadium source, a phosphorus source, a sodium source, a fluorine source, a carbon source and an aqueous phase, and performing a dispersion treatment to prepare a precursor slurry;
[0018] Drying and calcining the precursor slurry to prepare a phosphate positive electrode material;
[0019] The carbon source includes a first carbon source and a second carbon source, the first carbon source and the second carbon source each independently include one or more of glucose, polyethylene glycol, sucrose and ascorbic acid, and the first carbon source and the second carbon source are different.
[0020] In the technical solution of the embodiment of the present application, at least two carbon sources are selected for carbon coating treatment, thereby forming a carbon layer with high crystallinity on the inner core surface of the phosphate positive electrode material, giving it better electronic conductivity and structural stability, and significantly improving the compaction density and BET specific surface area of the phosphate positive electrode material, which is beneficial to improve the electrical properties such as specific capacity and rate performance of the secondary battery prepared using the phosphate positive electrode material, and further prepare a high energy density secondary battery.
[0021] In some embodiments, the first carbon source is glucose and the second carbon source comprises one or more of polyethylene glycol, sucrose, and ascorbic acid.
[0022] In this embodiment, glucose is used as the first carbon source and is compounded with at least one of polyethylene glycol, sucrose and ascorbic acid, which is conducive to forming a carbon layer with high crystallinity and ensures that the material has a high compaction density, a high BET specific surface area and excellent electrochemical properties.
[0023] In some embodiments, the mass ratio of the first carbon source to the second carbon source is (1-6):1.
[0024] In this embodiment, by controlling the ratio of the two carbon sources, a good balance can be achieved among compaction density, BET specific surface area and electrochemical performance, thereby obtaining a phosphate positive electrode material having high compaction density, high BET specific surface area and excellent electrochemical performance.
[0025] In some embodiments, the molar ratio of vanadium in the vanadium source, phosphorus in the phosphorus source, sodium in the sodium source, fluorine in the fluorine source, and carbon in the carbon source is 1:(0.8-1.2):(1.4-1.6):(1.4-1.6):(0.45-0.55).
[0026] In this embodiment, by controlling the molar ratio of each element in the raw material, the raw materials can be fully reacted to form a high-purity sodium vanadium fluorophosphate material, and a carbon layer with a suitable thickness and carbon content is formed on the surface thereof.
[0027] In some embodiments, the vanadium source includes one or more of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, sodium metavanadate and sodium orthovanadate; and / or, the phosphorus source includes one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and sodium phosphate; and / or, the sodium source includes one or more of sodium fluoride, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate; and / or, the fluorine source includes one or more of sodium fluoride and ammonium fluoride.
[0028] In this embodiment, different vanadium sources, phosphorus sources, sodium sources and fluorine sources have different reactivity. Through the rational selection and combination of different raw materials, the reaction rate of the high-temperature solid-phase synthesis reaction can be regulated, the stoichiometric ratio of the phosphate positive electrode material can be accurately controlled, and the crystal structure and surface morphology of the material can be optimized, thereby improving its electrochemical performance.
[0029] In some embodiments, the dispersion process includes one or more of a ball milling process and a sand milling process.
[0030] In this embodiment, ball milling and / or sand milling can be used to make different materials evenly mixed and fully contacted, and the D50 particle size of the precursor slurry can be reduced, which is beneficial to improving the subsequent reaction rate and product uniformity.
[0031] In some embodiments, the solid content of the precursor slurry is 20% to 30%; and / or the D50 particle size of the precursor slurry is 0.4 μm to 0.6 μm.
[0032] In this embodiment, regulating the solid content of the precursor slurry can regulate the evaporation rate of water during drying, improve production efficiency and reduce energy consumption, and promote the conversion of the precursor slurry into a dry material with a relatively uniform particle size distribution; regulating the D50 particle size of the precursor slurry can improve the dispersion uniformity and stability of the raw materials, optimize the particle size distribution of the dry material, and help improve the reaction uniformity during the calcination process, thereby improving the electrochemical properties of the material.
[0033] In some embodiments, the drying process includes the following steps: spray drying the precursor slurry, the inlet air temperature of the spray drying is 240°C to 260°C, and the outlet air temperature is 90°C to 100°C to obtain a dried material.
[0034] In this embodiment, the inlet air temperature and outlet air temperature of the spray drying are controlled to fully remove the moisture in the drying material and avoid excessively high outlet air temperature causing partial decomposition of the carbon source and reducing the carbon content of the product.
[0035] In some embodiments, the calcination treatment comprises the following steps: in a protective atmosphere, heating to 550° C. to 750° C. and maintaining the temperature for 6 h to 12 h.
[0036] In this embodiment, high-temperature calcination in a protective atmosphere can avoid the reaction of the material with moisture and oxygen during the heating, insulation and cooling stages, which is beneficial to improving the purity of the finished product and reducing the adverse effects on the subsequent preparation process and electrical properties of the positive electrode sheet and secondary battery. Calcination at a temperature of 550°C to 750°C is beneficial to avoid the formation of too many impurities during the sintering process due to excessively high or low temperatures, which helps to improve the crystallinity of the finished product, thereby improving the charge and discharge specific capacity. The insulation time is 6h to 12h, which helps to ensure the purity of the finished product and the uniformity of the carbon coating, thereby improving the electrical properties of the material.
[0037] In some embodiments, after the calcination treatment, the following steps are further included: pulverizing, screening and iron removal treatment of the calcined product to prepare a phosphate positive electrode material with a D50 particle size of 4 μm to 10 μm.
[0038] In this embodiment, by controlling the D50 particle size of the phosphate positive electrode material, it is beneficial to + It can quickly transport the positive electrode and improve its uniformity of dispersion in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the consistency and stability of the positive electrode sheet.
[0039] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the phosphate positive electrode material provided in the first aspect of the present application, or comprising a phosphate positive electrode material prepared by the preparation method of the phosphate positive electrode material provided in the second aspect of the present application.
[0040] In this embodiment, the positive electrode plate includes the above-mentioned phosphate positive electrode material, which is beneficial to improving the specific capacity and rate performance of the secondary battery prepared using the positive electrode plate.
[0041] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.
[0042] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high specific capacity and good rate performance.
[0043] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0045] Figure 1 Schematic diagram of a process for preparing a phosphate positive electrode material in one embodiment of the present application;
[0046] Figure 2 This is a phase result diagram of the phosphate positive electrode material of Example 1 of the present application;
[0047] Figure 3 This is a phase result diagram of the phosphate positive electrode material of Comparative Example 1 of the present application;
[0048] Figure 4 This is a phase result diagram of the phosphate positive electrode material of Comparative Example 2 of the present application;
[0049] Figure 5 This is a morphology result diagram of the phosphate positive electrode material of Example 1 of the present application;
[0050] Figure 6 This is a morphology result diagram of the phosphate positive electrode material of Comparative Example 1 of the present application;
[0051] Figure 7 This is a morphology result diagram of the phosphate positive electrode material of Comparative Example 2 of the present application;
[0052] Figure 8 This is a Raman spectrum of the phosphate positive electrode material of Example 1 of the present application. DETAILED DESCRIPTION
[0053] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0055] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0057] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0058] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0059] the term
[0060] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0061] Particle size: For spherical particles, the particle size refers to the diameter of the spherical particles. For non-spherical particles, such as particles with an olivine morphology, the particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as the particle size), and the particle size measured by the laser particle size analyzer is the equivalent diameter of the particle. Among them, the equivalent particle size refers to when a certain physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.
[0062] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N = 0 to 100. When N = 100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N = 50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles with a particle size smaller than 1mm and particles with a particle size larger than 1mm each account for 50% of all particles.
[0063] Crystallinity of carbon materials: Carbon materials have two characteristic peaks in Raman spectra: D peak and G peak. Among them, D peak is usually at 1350cm -1 It is related to the disordered structure and defects of carbon materials; the G peak is usually at 1580cm -1 The intensity ratio of D peak to G peak is denoted as I D / I G , which can characterize the crystallinity of carbon materials; I D / I G When the value of is low, it indicates that the crystallinity of the carbon material is high and the proportion of graphitized structure is higher; D / I G When the value is high, it indicates that the carbon material has low crystallinity and contains more disordered structures and defects.
[0064] The demand for capacity and compaction density of sodium-ion batteries (SIBs) in the commercialization process is getting higher and higher. High capacity and high compaction density mean higher energy density after being assembled into a battery. At present, the electrode materials of SIBs face some huge challenges, such as difficult-to-overcome structural instability, slow ion diffusion, low operating voltage, and low energy / power density. In order to solve these problems, researchers are mainly committed to designing and preparing new electrode materials with high adaptability and reversibility in the process of large sodium ion intercalation / extraction. Transition metal oxides (TMOs) and polyanionic compounds (PACs) with layered structures are the two most promising candidate materials for the positive electrode materials of SIBs. The theoretical capacity of PAC materials is slightly lower than that of TMO materials (such as NaMnO2, P2-Na 2 / 3 Fe 1 / 2 Mn 1 / 2O2 and vanadium oxide, etc.), but PAC materials usually have better cycle life than TMO materials and can meet the requirements of grid-level energy storage for ultra-long cycle life. Therefore, if the comprehensive electrochemical performance of PAC materials (including high-rate capability, specific capacity and operating voltage) is improved, its application prospects in SIBs will be very broad.
[0065] Sodium Super Ionic Conductor (NASICON) is one of the representative PAC materials, in which there is a stable three-dimensional (3D) open framework composed of PO tetrahedrons and MO octahedrons (M represents transition metal), which can realize Na + Rapid migration. Sodium vanadium phosphate (Na3V2(PO4)3, NVP) is the most typical NASICON material, with a theoretical capacity of 117.6mAh / g and an operating voltage of 3.3V~3.4V. It can provide a material-based energy density of about 394Wh / kg, which is significantly lower than the theoretical value of phosphate cathode materials in LIBs. Therefore, a major challenge facing phosphate cathode materials used in SIBs is to improve energy density to narrow the gap between theoretical energy density and actual energy density. In order to achieve higher energy density for phosphate cathode materials, increasing the operating voltage is usually more effective and easier than adjusting the capacity, because it is very difficult to reduce the molecular weight of each electron transfer. Compared with NVP without fluorine, NASICON materials doped with fluorine usually have higher operating voltages. For example, sodium vanadium fluorophosphate (Na3V2(PO4)2F3, NVPF) can provide an average operating voltage of up to 3.95V, a theoretical capacity of 128mAh / g, and a corresponding theoretical energy density of up to ~507Wh / kg. Therefore, NVPF is a more attractive and promising high energy density NASICON material for SIBs. However, as a member of the NASICON family, NVPF also inherits the defect of low electronic conductivity, which limits its capacity and rate performance and hinders it from achieving comprehensive excellent electrochemical performance including high energy density.
[0066] In order to solve the technical problem that traditional phosphate positive electrode materials have poor electronic conductivity, which limits their performance in discharge capacity and rate performance, the present application provides a phosphate positive electrode material and its preparation method, a positive electrode plate and a secondary battery, wherein the phosphate positive electrode material is coated with a carbon layer with high crystallinity on the surface of the sodium vanadium fluorophosphate material, which not only gives it better electronic conductivity and structural stability, but also improves its compaction density and BET specific surface area, thereby improving the specific capacity and rate performance of the positive electrode plate and the secondary battery.
[0067] In a first aspect, an embodiment of the present application provides a phosphate cathode material, the phosphate cathode material comprising an inner core and a carbon layer covering the inner core; the inner core comprises a sodium vanadium fluorophosphate material; wherein the compacted density of the phosphate cathode material is ≥1.78 g / cm 3 , BET specific surface area ≥9m 2 / g; The Raman spectrum of the phosphate positive electrode material has a D peak and a G peak, and the intensity ratio of the D peak to the G peak is (1.03~1.05):1.
[0068] In the technical solution of the embodiment of the present application, the phosphate positive electrode material has a sodium vanadium fluorophosphate material with a high working voltage as the core, and is coated with a carbon layer with high crystallinity on the core, which not only gives it better electronic conductivity and structural stability, but also improves its compaction density and BET specific surface area, which is beneficial to improve the specific capacity and rate performance of the secondary battery prepared using the phosphate positive electrode material, and thus obtain a secondary battery with high energy density.
[0069] In this embodiment, the compaction density of the phosphate positive electrode material is ≥1.78 g / cm 3 , including but not limited to 1.78g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 or 2.5g / cm 3 , more preferably 1.94 g / cm 3 ~2.06g / cm 3 Among them, the phosphate cathode material has a higher compaction density, which can improve the specific capacity and rate performance of the secondary battery prepared using the phosphate cathode material.
[0070] In this embodiment, the BET specific surface area of the phosphate positive electrode material is ≥9m 2 / g, including but not limited to 9m 2 / g, 9.5m 2 / g, 9.8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 24m 2 / g, 26m2 / g, 28 m 2 / g or 30 m 2 / g, more preferably 9.8 m 2 / g to 16 m 2 / g. Among them, the phosphate cathode material has a relatively moderate specific surface area, which means that it has more active sites for electrochemical reactions to occur, and at the same time can improve the lithium ion transmission rate, so that the secondary battery prepared with the phosphate cathode material can exhibit higher specific capacity and better rate performance.
[0071] In this embodiment, the intensity ratio (I D / I G ) of the D peak and the G peak of the phosphate cathode material in the Raman spectrum is (1.03 - 1.05):1, including but not limited to 1.03:1, 1.032:1, 1.034:1, 1.036:1, 1.038:1, 1.04:1, 1.042:1, 1.044:1, 1.046:1, 1.048:1 or 1.05:1. Among them, the value of I D / I G of the phosphate cathode material in the Raman spectrum is relatively low, indicating that the crystallinity of its carbon layer is relatively high, which can improve its electron conductivity and structural stability, thereby improving the specific capacity, rate performance and cycle performance of the secondary battery prepared with this phosphate cathode material.
[0072] In some embodiments, the expression of the sodium vanadium fluorophosphate material is: Na 3+x+y V 2-x-y A x B y (PO4)2F3; where 0 ≤ x ≤ 0.5, 0 ≤ y ≤ 0.5; element A and element B each independently include one of Fe, Mn, Ti, Al and Mg, and element A and element B are different from each other.
[0073] In this embodiment, both x and y represent stoichiometric ratios, and the values of x and y can each independently be 0, 0.01, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5. Preferably, 0 < x ≤ 0.5, 0 < y ≤ 0.5.
[0074] It can be understood that if x = 0 and y = 0, the expression of the sodium vanadium fluorophosphate material is Na3V2(PO4)2F3 (NVPF), which means that this sodium vanadium fluorophosphate material does not contain any doped metal cations. If x = 0 or y = 0, this sodium vanadium fluorophosphate material is doped with a single metal cation. If 0 < x ≤ 0.5 and 0 < y ≤ 0.5, this sodium vanadium fluorophosphate material is doped with two different metal cations, thus forming high-entropy doping.
[0075] In this embodiment, by doping with metal cations of a specific type and a specific ratio, the sodium vanadium fluorophosphate material can be made to melt more completely during the high-temperature sintering process, making the surface morphology more compact, thereby improving the compaction density, BET specific surface area and specific capacity of the sodium vanadium fluorophosphate material. Specifically, compared with NVPF without metal cation doping, after doping the sodium vanadium fluorophosphate material with metal cations of high voltage platforms such as Fe, Mn, Ti, Al and Mg, the average voltage platform and specific capacity of the material are effectively improved. Among them, the ionic radius of Fe, Mn, Ti, Al and Mg are all similar to V 3+ The ionic radius (0.062nm) is similar, which is conducive to expanding the Na + The diffusion channel of Na+ can be inhibited, thereby reducing the voltage decay caused by the phase change. At the same time, the doping of multiple metal cations can also increase the Na+ + The diffusion rate of sodium vanadium fluorophosphate is increased, and the ionic conductivity of the sodium vanadium fluorophosphate material is improved, thereby improving the specific capacity and rate performance of the sodium vanadium fluorophosphate material.
[0076] In some embodiments, the mass ratio of the inner core and the carbon layer is 100:(1.75-3.3), including but not limited to 100:1.75, 100:1.8, 100:1.9, 100:2, 100:2.1, 100:2.2, 100:2.3, 100:2.4, 100:2.5, 100:2.6, 100:2.7, 100:2.8, 100:2.9, 100:3, 100:3.1, 100:3.2, or 100:3.3. Preferably, the mass ratio of the inner core and the carbon layer is 100:(2-3).
[0077] In this embodiment, by controlling the mass ratio of the core and the carbon layer, higher electronic conductivity can be achieved to improve the specific capacity, rate performance and cycle performance of the prepared phosphate positive electrode material. If the mass ratio of the carbon layer is too low, an effective coating structure and conductive network cannot be formed, and the effect of improving electronic conductivity is not ideal; if the mass ratio of the carbon layer is too high, the content of electrochemically active substances will be reduced, the material resistance will be increased, and the Na + diffusion, thereby reducing the comprehensive electrochemical performance of the prepared phosphate cathode material.
[0078] In some embodiments, the thickness of the carbon layer is 1 nm to 3 nm, including but not limited to 1 nm, 1.2 nm, 1.5 nm, 1.8 nm, 2 nm, 2.2 nm, 2.5 nm, 2.8 nm or 3 nm. Preferably, the thickness of the carbon layer is 1.95 nm to 2.8 nm.
[0079] In this embodiment, controlling the thickness of the carbon layer within a suitable range can improve electronic conductivity, enhance structural stability, and inhibit side reactions, thereby improving the specific capacity, rate performance, and cycle performance of the prepared phosphate positive electrode material.
[0080] In some embodiments, the D50 particle size of the phosphate positive electrode material is 4 μm to 10 μm, including but not limited to 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm. Preferably, the D50 particle size of the phosphate positive electrode material is 5 μm to 6 μm.
[0081] In this embodiment, the phosphate positive electrode material has a suitable particle size to ensure that Na + It can be embedded and released relatively quickly, thereby effectively improving the specific capacity and rate performance of secondary batteries prepared with phosphate positive electrode materials. At the same time, because phosphate positive electrode materials are easily dispersed in electrode slurry, it is beneficial to form a positive electrode active coating with high flatness and good uniformity, which is beneficial to improve the consistency and stability of positive electrode sheets prepared with phosphate positive electrode materials.
[0082] Please refer to Figure 1 In a second aspect, the present application provides a method for preparing a phosphate positive electrode material, comprising the following steps:
[0083] S1: mixing a vanadium source, a phosphorus source, a sodium source, a fluorine source, a carbon source and an aqueous phase, and performing a dispersion treatment to prepare a precursor slurry;
[0084] S2: drying and calcining the precursor slurry to prepare a phosphate positive electrode material;
[0085] The carbon source includes a first carbon source and a second carbon source, the first carbon source and the second carbon source each independently include one or more of glucose, polyethylene glycol, sucrose and ascorbic acid, and the first carbon source and the second carbon source are different.
[0086] In the technical solution of the embodiment of the present application, at least two carbon sources are selected for carbon coating treatment, thereby forming a carbon layer with high crystallinity on the inner core surface of the phosphate positive electrode material, giving it better electronic conductivity and structural stability, and significantly improving the compaction density and BET specific surface area of the phosphate positive electrode material, which is beneficial to improve the specific capacity and rate performance of the secondary battery prepared using the phosphate positive electrode material, and further prepare a high energy density secondary battery.
[0087] The following is a detailed description of the preparation method of the phosphate positive electrode material in a step-by-step manner.
[0088] S1: Mix a vanadium source, a phosphorus source, a sodium source, a fluorine source, a carbon source and water, and grind them to prepare a precursor slurry.
[0089] In some embodiments, the molar ratio of vanadium in the vanadium source, phosphorus in the phosphorus source, sodium in the sodium source, fluorine in the fluorine source, and carbon in the carbon source is 1:(0.8-1.2):(1.4-1.6):(1.4-1.6):(0.45-0.55).
[0090] In this embodiment, by controlling the molar ratio of each element in the raw material, the raw materials can be fully reacted to form a high-purity sodium vanadium fluorophosphate material, and a carbon layer with a suitable thickness and carbon content is formed on its surface. Specifically, the molar ratio of the vanadium element in the vanadium source and the phosphorus element in the phosphorus source can be 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.2 or any ratio within the range of 1:(0.8-1.2); the molar ratio of the vanadium element in the vanadium source and the sodium element in the sodium source, and the molar ratio of the vanadium element in the vanadium source and the fluorine element in the fluorine source, can each independently be 1:1.4, 1:1.42, 1:1.44, 1:1.46, 1:1.4 8. 1:1.5, 1:1.52, 1:1.54, 1:1.56, 1:1.58, 1:1.6 or any ratio in the range of 1:(1.4-1.6); the molar ratio of the vanadium element in the vanadium source to the carbon element in the carbon source can be 1:0.45, 1:0.46, 1:0.47, 1:0.48, 1:0.49, 1:0.50, 1:0.51, 1:0.52, 1:0.53, 1:0.54, 1:0.55 or any ratio in the range of 1:(0.45-0.55).
[0091] In some embodiments, the vanadium source includes one or more of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, sodium metavanadate and sodium orthovanadate. It is understandable that the vanadium source can be selected from any one of the above vanadium sources, or a combination of at least two of them, for example: a combination of vanadium pentoxide and vanadium trioxide, a combination of vanadium pentoxide and vanadium dioxide, a combination of vanadium pentoxide and ammonium metavanadate, a combination of vanadium pentoxide and sodium metavanadate, a combination of vanadium pentoxide and sodium orthovanadate, a combination of vanadium pentoxide, vanadium trioxide, vanadium dioxide and ammonium metavanadate, etc. Preferably, the vanadium source is vanadium pentoxide.
[0092] In some embodiments, the phosphorus source includes one or more of diammonium hydrogen phosphate, monoammonium phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate. It is understandable that the phosphorus source can be selected from any one of the above phosphorus sources, or a combination of at least two thereof, for example: a combination of diammonium hydrogen phosphate and diammonium hydrogen phosphate, a combination of diammonium hydrogen phosphate and ammonium phosphate, a combination of diammonium hydrogen phosphate and disodium hydrogen phosphate, a combination of diammonium hydrogen phosphate and sodium dihydrogen phosphate, a combination of diammonium hydrogen phosphate, diammonium dihydrogen phosphate, and ammonium phosphate, etc. Preferably, the phosphorus source is diammonium hydrogen phosphate.
[0093] In some embodiments, the sodium source includes one or more of sodium fluoride, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate. It is understandable that the sodium source can be selected from any one of the above sodium sources, or a combination of at least two thereof, for example: a combination of sodium fluoride and sodium hydroxide, a combination of sodium fluoride and sodium carbonate, a combination of sodium fluoride and sodium bicarbonate, a combination of sodium fluoride and sodium nitrate, a combination of sodium fluoride and sodium acetate, a combination of sodium fluoride and sodium dihydrogen phosphate, a combination of sodium fluoride and disodium hydrogen phosphate, a combination of sodium fluoride and sodium phosphate, a combination of sodium fluoride, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate, etc. Preferably, the sodium source is sodium fluoride.
[0094] In some embodiments, the fluorine source includes one or more of sodium fluoride and ammonium fluoride. It is understood that the fluorine source can be selected from sodium fluoride, ammonium fluoride, and a combination of sodium fluoride and ammonium fluoride. Preferably, the fluorine source is sodium fluoride.
[0095] In this embodiment, different vanadium sources, phosphorus sources, sodium sources and fluorine sources have different reactivity. Through the rational selection and combination of different raw materials, the reaction rate of the high-temperature solid-phase synthesis reaction can be regulated, the stoichiometric ratio of the phosphate positive electrode material can be accurately controlled, and the crystal structure and surface morphology of the material can be optimized, thereby improving its electrochemical performance.
[0096] In some embodiments, the first carbon source is glucose, and the second carbon source includes one or more of polyethylene glycol, sucrose and ascorbic acid. It is understandable that the second carbon source can be selected from any one of polyethylene glycol, sucrose and ascorbic acid, or at least two of polyethylene glycol, sucrose and ascorbic acid, for example: a combination of polyethylene glycol and sucrose, a combination of polyethylene glycol and ascorbic acid, a combination of sucrose and ascorbic acid, a combination of polyethylene glycol, sucrose and ascorbic acid. Wherein, the molecular weight of polyethylene glycol can be 100 to 10000, for example, 100, 200, 400, 600, 800, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000, preferably, the molecular weight of polyethylene glycol is 2000 to 6000.
[0097] Through research, this application found that the carbon layer structure obtained by calcining different carbon sources at high temperature has obvious differences, which has a very large impact on the compaction density, BET specific surface area and electrochemical performance of phosphate positive electrode materials. Using glucose as the first carbon source and compounding it with at least one of polyethylene glycol, sucrose and ascorbic acid is conducive to forming a carbon layer with high crystallinity, and ensures that the prepared phosphate positive electrode material has high compaction density, high BET specific surface area and excellent electrochemical performance.
[0098] Please refer to Table 1. When glucose is used as the carbon source, the carbon layer formed has the characteristics of finer particles and denser surface, so the compaction density is higher and the BET specific surface area is smaller. However, the high surface density is not conducive to Na + The diffusion of ions leads to poor electrochemical performance of the prepared phosphate cathode material.
[0099] Furthermore, when polyethylene glycol (PEG) is used as a carbon source, polyethylene glycol, as a polymer carbon source, is easily not completely broken due to the low sintering temperature, thereby forming a carbon layer with a network structure, which can promote the penetration of electrolyte and improve electronic conductivity. Therefore, the compaction density is low, the BET specific surface area is large, and the electrochemical performance is better.
[0100] Furthermore, when sucrose is used as the carbon source, it will first be converted into caramel with higher viscosity during the low-temperature heating stage, which will inhibit the crystal growth of the material and show a needle-like and flocculent structure, resulting in low crystallinity of the carbon layer, poor electronic conductivity and structural stability. Therefore, the compaction density is high, the BET specific surface area is between glucose and PEG, and the electrochemical performance is poor.
[0101] Furthermore, when ascorbic acid, also known as vitamin C (VC), is used as the carbon source, the formed carbon layer has larger particles, and too many particles will lead to an unstable carbon layer structure. Therefore, the compaction density and BET specific surface area are between sucrose and PEG, and the electrochemical performance is poor.
[0102] Table 1. Effects of different carbon sources on the performance of phosphate cathode materials
[0103]
[0104] In some embodiments, the mass ratio of the first carbon source to the second carbon source is (1-6):1, including but not limited to 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1.
[0105] In this embodiment, by controlling the ratio of the two carbon sources, a good balance can be achieved among compaction density, BET specific surface area and electrochemical performance, thereby obtaining a phosphate positive electrode material having high compaction density, high BET specific surface area and excellent electrochemical performance.
[0106] In some embodiments, the water may be selected from one or more of distilled water, reverse osmosis water, deionized water, pure water and ultrapure water. Preferably, the water is deionized water.
[0107] In some embodiments, the dispersion process includes one or more of a ball milling process and a sand milling process.
[0108] In this embodiment, ball milling and / or sand milling can be used to make different materials evenly mixed and fully contacted, and the D50 particle size of the precursor slurry can be reduced, which is beneficial to improving the subsequent reaction rate and product uniformity.
[0109] In some embodiments, the dispersion treatment comprises the following steps: putting a mixture containing a vanadium source, a phosphorus source, a sodium source, a fluorine source, a carbon source and water into a ball mill, and ball milling for 1 h to 3 h at an operating frequency of 10 Hz to 50 Hz to obtain a ball milled slurry; putting the ball milled slurry into a sand mill, and grinding the slurry at a main machine speed of 400 rpm to 1300 rpm and a circulation flow rate of 2000 m 3 / h~5000m 3 The precursor slurry is obtained by sand milling for 1 h to 3 h under the condition of 200 g / min and 100 g / min.
[0110] In some embodiments, the solid content of the precursor slurry is 20% to 30%, including but not limited to 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value within the range of 20% to 30%.
[0111] In this embodiment, regulating the solid content of the precursor slurry can regulate the evaporation rate of water during drying, improve production efficiency and reduce energy consumption, and promote the conversion of the precursor slurry into a dry material with a relatively uniform particle size distribution, which is beneficial to improving the reaction uniformity during the calcination process, thereby improving the electrochemical properties of the material.
[0112] In some embodiments, the D50 particle size of the precursor slurry is 0.4 μm to 0.6 μm, including but not limited to 0.4 μm, 0.42 μm, 0.45 μm, 0.48 μm, 0.5 μm, 0.52 μm, 0.55 μm, 0.58 μm, 0.6 μm or any value within the range of 0.4 μm to 0.6 μm. Preferably, the D50 particle size of the precursor slurry is 0.4 μm.
[0113] In this embodiment, the D50 particle size of the precursor slurry is regulated to improve the dispersion uniformity and stability of the raw materials, optimize the particle size distribution of the dried material, and help improve the reaction uniformity during the calcination process, thereby improving the electrochemical performance of the material.
[0114] S2: drying and calcining the precursor slurry to prepare a phosphate positive electrode material;
[0115] In some embodiments, the drying process includes the following steps: spray drying the precursor slurry, the inlet air temperature of the spray drying is 240°C to 260°C, and the outlet air temperature is 90°C to 100°C to obtain a dried material.
[0116] In this embodiment, the air inlet temperature of the spray drying can be 240°C, 242°C, 244°C, 246°C, 248°C, 250°C, 252°C, 254°C, 256°C, 258°C, 260°C or any value in the range of 240°C to 260°C; the air outlet temperature of the spray drying can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C or any value in the range of 90°C to 100°C. By controlling the air inlet temperature and air outlet temperature of the spray drying, the moisture in the drying material can be fully removed, and the excessively high air outlet temperature can be avoided to cause partial decomposition of the carbon source and reduce the carbon content of the product.
[0117] In some embodiments, the calcination treatment includes the following steps: in a protective atmosphere, heating the dried material to 550° C. to 750° C. and maintaining the temperature for 6 h to 12 h.
[0118] In this embodiment, the protective gas in the protective atmosphere can be at least one of nitrogen, helium, neon, argon and xenon, preferably, the protective gas is nitrogen or argon. High-temperature calcination in a protective atmosphere can avoid the reaction of the material with moisture and oxygen during the heating, insulation and cooling stages, which is beneficial to improving the purity of the finished product and reducing the adverse effects on the subsequent preparation process and electrical properties of the positive electrode sheet and the secondary battery.
[0119] In this embodiment, the calcination temperature can be 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃ or any value in the range of 550℃~750℃. Calcination at a temperature of 550℃~750℃ is beneficial to avoid excessive formation of impurities during sintering due to excessively high or low temperature, which helps to improve the crystallinity of the finished product, thereby improving the charge-discharge specific capacity. Preferably, the calcination temperature is 550℃~650℃. Calcination at a temperature of 550℃~650℃ can reduce the energy consumption of the calcination process while ensuring the crystallinity and charge-discharge specific capacity of the finished product, thereby reducing the cost of the phosphate positive electrode material.
[0120] In this embodiment, the holding time can be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h or any value within the range of 6h to 12h. The holding time is 6h to 12h, which helps to ensure the purity of the finished product and the uniformity of the carbon coating, thereby improving the electrochemical performance of the material. Preferably, the holding time is 8h to 12h.
[0121] In some embodiments, after the calcination treatment, the following steps are further included: pulverizing, screening and iron removal treatment of the calcined product to prepare a phosphate positive electrode material with a D50 particle size of 4 μm to 10 μm.
[0122] In this embodiment, the D50 particle size of the phosphate positive electrode material can be 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm. Preferably, the D50 particle size of the phosphate positive electrode material is 5 μm to 6 μm. By controlling the D50 particle size of the phosphate positive electrode material, it is beneficial to + It can improve the rapid transmission of the phosphate positive electrode material and its uniformity of dispersion in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the consistency and stability of the positive electrode sheet prepared with the phosphate positive electrode material.
[0123] In some embodiments, the D100 particle size of the phosphate positive electrode material is ≤30 μm.
[0124] In some embodiments, during the crushing, screening and iron removal processes, the ambient humidity is ≤10%.
[0125] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising the phosphate positive electrode material provided in the first aspect of the present application, or comprising a phosphate positive electrode material prepared by the preparation method of the phosphate positive electrode material provided in the second aspect of the present application.
[0126] In this embodiment, the positive electrode plate includes the above-mentioned phosphate positive electrode material, and thus has the advantages of high specific capacity and good rate performance.
[0127] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode plate provided in the third aspect of the present application.
[0128] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantages of high specific capacity and good rate performance.
[0129] In some embodiments, the first charge specific capacity of the secondary battery at 0.1C is ≥109mAh / g, including but not limited to 109mAh / g, 110mAh / g, 112mAh / g, 114mAh / g, 116mAh / g, 118mAh / g, 120mAh / g, 122mAh / g, 124mAh / g, 126mAh / g, 128mAh / g or 130mAh / g, and is further preferably 122mAh / g to 128mAh / g.
[0130] In some embodiments, the first discharge specific capacity of the secondary battery at 0.1C is ≥95mAh / g, including but not limited to 95mAh / g, 96mAh / g, 98mAh / g, 100mAh / g, 102mAh / g, 104mAh / g, 106mAh / g, 108mAh / g, 110mAh / g, 112mAh / g, 114mAh / g, 116mAh / g, 118mAh / g or 120mAh / g, and is further preferably 113mAh / g to 117mAh / g.
[0131] In some embodiments, the first coulombic efficiency of the secondary battery at 0.1C is ≥87%, including but not limited to 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, and is further preferably 91.31% to 92.74%.
[0132] In some embodiments, the first discharge specific capacity of the secondary battery at 1C is ≥84mAh / g, including but not limited to 84mAh / g, 86mAh / g, 88mAh / g, 90mAh / g, 92mAh / g, 95mAh / g, 98mAh / g, 100mAh / g, 102mAh / g, 105mAh / g, 108mAh / g, 110mAh / g, 112mAh / g or 115mAh / g, and is further preferably 107mAh / g to 112mAh / g.
[0133] In some embodiments, the 1C / 0.1C rate performance of the secondary battery is ≥88%, including but not limited to 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100%, and is further preferably 93.91% to 95.72%.
[0134] In this embodiment, the secondary battery has high specific charge capacity, specific discharge capacity, first coulombic efficiency and rate performance, which is beneficial to improving the electrochemical performance of the electrical device using the secondary battery.
[0135] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0136] 1. Preparation method
[0137] Example 1
[0138] Please refer to Table 2. The preparation method of the phosphate positive electrode material of this embodiment is as follows:
[0139] (1) Mix a vanadium source, a phosphorus source, a sodium source, a fluorine source and a carbon source, add deionized water, and obtain a mixture with a solid content of 25%; put the mixture into a ball mill for coarse grinding, and ball mill for 2 hours at an operating frequency of 30 Hz to make the materials evenly mixed to obtain a ball mill slurry; transfer the ball mill slurry to a sand mill for fine grinding, and sand mill for 2 hours at a rotation speed of 1000 rpm and a circulation flow rate of 3000 to obtain a precursor slurry with a D50 particle size of 0.4 μm.
[0140] Among them, the vanadium source is vanadium pentoxide, the phosphorus source is diammonium hydrogen phosphate, the sodium source and the fluorine source are both sodium fluoride, the carbon source is glucose and PEG-2000 with a mass ratio of 4:1, and the molar ratio of vanadium, phosphorus, sodium, fluorine and carbon is 1:1:1.5:1.5:0.5.
[0141] (2) The precursor slurry is spray dried, and the inlet air temperature is controlled at 250°C and the outlet air temperature is controlled at 90°C to obtain a dried material; the dried material is transferred into a sintering furnace, dry nitrogen is introduced as a protective gas, the temperature is raised to 600°C and kept warm for 10 hours to obtain a sintered material; the sintered material is crushed, sieved and iron-removed to obtain a phosphate positive electrode material with a D50 particle size of 5.1 μm and a D100 particle size of <30 μm.
[0142] Embodiments 2 to 14
[0143] Embodiments 2 to 14 are substantially the same as Embodiment 1, except that the differences are as follows:
[0144] Example 2: The carbon source is selected from glucose and PEG-2000 in a mass ratio of 6:1;
[0145] Example 3: The carbon source is selected from glucose and PEG-2000 in a mass ratio of 5:1;
[0146] Example 4: The carbon source is selected from glucose and PEG-2000 in a mass ratio of 3:1;
[0147] Example 5: The carbon source is selected from glucose and PEG-2000 in a mass ratio of 2:1;
[0148] Example 6: The carbon source is selected from glucose and PEG-2000 in a mass ratio of 1:1;
[0149] Example 7: The carbon source is selected from glucose and PEG-2000 in a mass ratio of 1:2;
[0150] Example 8: The carbon source is selected from glucose and sucrose in a mass ratio of 1:1;
[0151] Example 9: The carbon source is selected from glucose and sucrose in a mass ratio of 4:1;
[0152] Example 10: The carbon source is selected from glucose and sucrose in a mass ratio of 6:1;
[0153] Example 11: The carbon source is selected from glucose and VC in a mass ratio of 1:1;
[0154] Example 12: The carbon source is selected from glucose and VC in a mass ratio of 4:1;
[0155] Example 13: The carbon source is selected from glucose and VC in a mass ratio of 6:1;
[0156] Example 14: The carbon source is VC and PEG-2000 in a mass ratio of 4:1;
[0157] Example 15: In the process of mixing the vanadium source, phosphorus source, sodium source, fluorine source and carbon source, the molar ratio of vanadium element, phosphorus element, sodium element, fluorine element and carbon element is 1:1:1.5:1.5:0.4;
[0158] Example 16: In the process of mixing the vanadium source, phosphorus source, sodium source, fluorine source and carbon source, the molar ratio of vanadium element, phosphorus element, sodium element, fluorine element and carbon element is 1:1:1.5:1.5:0.6.
[0159] Comparative Examples 1 to 4
[0160] Comparative Examples 1 to 4 are substantially the same as Example 1, except that the differences are as follows:
[0161] Comparative Example 1: Glucose was selected as the carbon source;
[0162] Comparative Example 2: PEG-2000 was used as the carbon source;
[0163] Comparative Example 3: Sucrose was used as the carbon source;
[0164] Comparative Example 4: VC was selected as the carbon source;
[0165] 2. Test Method
[0166] 1. Property test of phosphate cathode materials
[0167] (1) X-ray diffraction (XRD) test: The phase analysis was performed using a Bruker D8Advance X-ray diffractometer produced by Bruker, Germany. The results are shown in Figures 2 to 4 .in, Figure 2 This is a phase result diagram of the phosphate positive electrode material of Example 1; Figure 3 This is a phase result diagram of the phosphate positive electrode material of Comparative Example 1; Figure 4 This is the physical phase result diagram of the phosphate positive electrode material of Comparative Example 2.
[0168] (2) Scanning electron microscopy (SEM) test: The morphology analysis was performed using a field emission scanning electron microscope (Merlin Compact and Quanta 200FEG) produced by Zeiss. The results are shown in Figures 5 to 7 . Figure 5 This is a morphology result diagram of the phosphate positive electrode material of Example 1; Figure 6 This is a morphology result diagram of the phosphate positive electrode material of Comparative Example 1; Figure 7 This is the morphology result diagram of the phosphate positive electrode material of Comparative Example 2.
[0169] (3) Transmission electron microscopy (TEM) test: A transmission electron microscope (TEM) of the model FEI Tecnai G2 F20 X-Twin produced by Thermo Fisher Scientific Inc. of the United States was used to perform morphological analysis and measure the thickness of the carbon layer. The results are shown in Table 3.
[0170] (4) Carbon content: The carbon content was tested using an infrared carbon-sulfur analyzer of model HCS-140 produced by Shanghai Dekai Company. The results are shown in Table 3.
[0171] (5) Raman test: Raman spectroscopy analysis was performed using an inVia Raman spectrometer produced by Renishaw, UK. The results are shown in Figure 8 and Table 3. Among them, Figure 8 This is the Raman spectrum of the phosphate positive electrode material of Example 1.
[0172] (6) Particle size test: The particle size analysis was performed using a Mastersizer 2000 laser particle size analyzer produced by Malvern Instruments Ltd., UK. The results are shown in Table 4.
[0173] (7) Compaction density: The compaction density was tested using the UTM7305 battery powder compaction density meter provided by Shenzhen Sansi Zongheng Technology Co., Ltd. The results are shown in Table 4.
[0174] (8) Specific surface area: The specific surface area was measured using a BELSORP MaxII specific surface area analyzer produced by Japan-Michiko BELCO. The results are shown in Table 4.
[0175] 2. Properties test of secondary batteries
[0176] The phosphate positive electrode material is mixed with conductive carbon black and PVDF binder in a mass ratio of 90:5:5 to obtain a positive electrode slurry; the positive electrode slurry is coated on an aluminum foil with a thickness of 12 μm to form a positive electrode slurry layer with a thickness of 80 μm; it is then placed in an oven at 110°C and dried for 10 hours. After drying, it is punched into circular pole pieces with a diameter of 15 mm, and rolled at a compact density of 1.8 g / cm3 to obtain positive electrode pieces.
[0177] Sodium hexafluorophosphate (NaPF6) is used as sodium salt, and ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) with a volume ratio of 1:1:1 are used as organic solvents. The sodium salt is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M; a pure sodium sheet with a purity of 99% is used as the counter electrode, and the battery is assembled with the positive electrode sheet and the electrolyte in the LG2400 / 1000TS glove box produced by Weige Gas Purification Technology (Suzhou) Co., Ltd. to obtain a button half-cell.
[0178] The CT3002A battery performance test system produced by Wuhan Blue Electric Electronic Technology Co., Ltd. was used to perform rate performance tests on button half-cells. The test temperature was 25°C, the voltage range was 2 to 4.35V, and the rate range was 0.1C to 3C. The results are shown in Table 4.
[0179] III. Analysis of test results of various embodiments and comparative examples
[0180] Table 2. Carbon sources and dopants for phosphate cathode materials
[0181]
[0182] Table 3. Carbon layer parameters of phosphate cathode materials
[0183]
[0184] Table 4. Performance comparison of phosphate cathode materials and corresponding secondary batteries
[0185]
[0186] Depend on Figure 2 to Figure 4 By comparison, it can be seen that compared with Comparative Examples 1 and 2, Example 1 uses glucose and PEG-2000 as a composite carbon source, and its phase result diagram has basically no impurity peaks at 2θ=35° and 37°, proving that the use of a composite carbon source can obtain a phosphate positive electrode material with higher purity. Figure 5 to Figure 7 From the comparison, it can be seen that when glucose is used as the single carbon source in Comparative Example 1, the carbon layer has multiple tiny single crystal particles and the surface is rugged; when PEG-2000 is used as the single carbon source in Comparative Example 2, the carbon layer presents a chain network structure; Example 1 uses glucose and PEG-2000 as the composite carbon source, and the carbon layer is composed of very fine particles and is accompanied by a less network structure, which has the advantages of a relatively flat surface, high density and good crystallinity.
[0187] From Tables 2 to 3 and Figure 8 It can be seen that the carbon layer morphology of the phosphate positive electrode materials of Examples 1 to 16 changes with the changes in the composition and mass ratio of the two carbon sources, the carbon layer thickness is between 1.4nm and 3.0nm, the carbon content is between 1.75% and 3.30%, the intensity ratio of the D peak to the G peak is 1.03 to 1.05, and has a high degree of crystallinity.
[0188] As shown in Table 4, in Examples 1 to 6, the first carbon source is glucose, the second carbon source is PEG-2000, and the mass ratio of the two is controlled in the range of (1 to 6): 1, so that the compaction density of the phosphate cathode material is 1.94 g / cm 3 ~2.06g / cm 3 , BET specific surface area is 9.8m 2 / g~16m 2 / g, having the advantages of high compaction density and large BET specific surface area. The secondary battery prepared by the phosphate positive electrode material of Examples 1 to 6 has a 0.1C first charge specific capacity of 122mAh / g to 128mAh / g, a 0.1C first discharge specific capacity of 113mAh / g to 117mAh / g, a 0.1C first coulombic efficiency of 91.31% to 92.74%, a 1C first discharge specific capacity of 107mAh / g to 112mAh / g, and a 1C / 0.1C rate performance of 93.91% to 95.72%, showing the characteristics of high specific capacity, high first coulombic efficiency and excellent rate performance. It can be seen that using glucose and PEG-2000 as a composite carbon source can significantly improve the compaction density and BET specific surface area of the prepared phosphate positive electrode material, thereby facilitating the improvement of the specific capacity, first coulombic efficiency and rate performance of the secondary battery prepared by the phosphate positive electrode material. Among them, when the mass ratio of glucose and PEG-2000 in Example 1 is controlled at 4:1, the compaction density of the prepared phosphate positive electrode material is the highest, and the secondary battery prepared using the phosphate positive electrode material has the highest 0.1C charge and discharge specific capacity, the highest 1C discharge specific capacity, and the highest 1C / 0.1C rate performance, and the most excellent overall performance.
[0189] Compared with Examples 1 to 6, the mass ratio of glucose to PEG-2000 in Example 7 is controlled at 1:2, resulting in a significant decrease in the compaction density and BET specific surface area of the prepared phosphate positive electrode material, resulting in a significant decrease in the 0.1C charge and discharge specific capacity, 0.1C first coulomb efficiency, 1C discharge specific capacity and 1C / 0.1C rate performance of the secondary battery prepared using the phosphate positive electrode material, which proves that the amount of glucose in the composite carbon source is too small, which is not conducive to improving the compaction density and BET specific surface area of the prepared phosphate positive electrode material, thereby resulting in the deterioration of the electrochemical performance of the secondary battery prepared using the phosphate positive electrode material.
[0190] Compared with Examples 1 to 7, Comparative Example 1 uses glucose as the sole carbon source, and Comparative Example 2 uses PEG-2000 as the sole carbon source, resulting in a significant decrease in the compacted density and BET specific surface area of the prepared phosphate positive electrode material, resulting in a significant decrease in the 0.1C charge-discharge specific capacity, 1C discharge specific capacity, and 1C / 0.1C rate performance of the secondary battery prepared using the phosphate positive electrode material. This proves that the carbon coating treatment using glucose and PEG-2000 as two carbon sources, and the reasonable control of the mass ratio of the two carbon sources, can significantly improve the compacted density and BET specific surface area of the phosphate positive electrode material, and ensure that the secondary battery prepared using the phosphate positive electrode material has excellent performance in charge-discharge specific capacity, first coulomb efficiency, and rate performance.
[0191] In Examples 8 to 10, the first carbon source is glucose, the second carbon source is sucrose, and the mass ratio of the two is controlled in the range of (1 to 6): 1, so that the compaction density of the phosphate positive electrode material is 1.944 g / cm 3 ~2.04g / cm 3 , BET specific surface area is 10m 2 / g~14.8m 2 / g, having the advantages of high compaction density and large BET specific surface area. The secondary battery prepared by using the phosphate positive electrode material of Examples 8 to 10 has a 0.1C first charge specific capacity of 121mAh / g to 125mAh / g, a 0.1C first discharge specific capacity of 112mAh / g to 115mAh / g, a 0.1C first coulombic efficiency of 90.32% to 92.56%, a 1C first discharge specific capacity of 105mAh / g to 110mAh / g, and a 1C / 0.1C rate performance of 93.75% to 95.40%, showing the characteristics of high specific capacity, high first coulombic efficiency and excellent rate performance. It can be seen that using glucose and sucrose as a composite carbon source can improve the compaction density and BET specific surface area of the prepared phosphate positive electrode material, thereby facilitating the improvement of the specific capacity, first coulombic efficiency and rate performance of the secondary battery prepared by using the phosphate positive electrode material. Compared with Comparative Examples 1 and 3, the compaction density and BET specific surface area of the phosphate positive electrode materials prepared in Examples 8 to 10 are significantly improved, which leads to a significant improvement in the 0.1C charge and discharge specific capacity, 1C discharge specific capacity and 1C / 0.1C rate performance of the secondary battery prepared using the phosphate positive electrode material. This proves that carbon coating treatment using glucose and sucrose as two carbon sources is also beneficial to improving the compaction density and BET specific surface area of the phosphate positive electrode material and the electrochemical performance of the secondary battery using the phosphate positive electrode material.
[0192] In Examples 11 to 13, the first carbon source is glucose, the second carbon source is VC, and the mass ratio of the two is controlled in the range of (1 to 6): 1, so that the compaction density of the phosphate positive electrode material is 1.95 g / cm 3 ~2.043g / cm 3 , BET specific surface area is 9.9m 2 / g~14.1m 2 / g, having the advantages of high compaction density and large BET specific surface area. The secondary battery prepared by using the phosphate positive electrode material of Examples 11 to 13 has a 0.1C first charge specific capacity of 120mAh / g to 122mAh / g, a 0.1C first discharge specific capacity of 109mAh / g to 111mAh / g, a 0.1C first coulombic efficiency of 90.83% to 90.98%, a 1C first discharge specific capacity of 102mAh / g to 106mAh / g, and a 1C / 0.1C rate performance of 93.57% to 95.49%, showing the characteristics of high specific capacity, high first coulombic efficiency and excellent rate performance. It can be seen that using glucose and VC as a composite carbon source can significantly improve the compaction density and BET specific surface area of the prepared phosphate positive electrode material, thereby facilitating the improvement of the specific capacity, first coulombic efficiency and rate performance of the secondary battery prepared by using the phosphate positive electrode material. Compared with Comparative Examples 1 and 4, the compaction density and BET specific surface area of the phosphate positive electrode materials prepared in Examples 11 to 13 are significantly improved, which leads to a significant improvement in the 0.1C charge and discharge specific capacity, 1C discharge specific capacity and 1C / 0.1C rate performance of the secondary battery prepared using the phosphate positive electrode material. This confirms that the carbon coating treatment using glucose and VC as two carbon sources is also beneficial to improving the compaction density and BET specific surface area of the material and the electrochemical performance of the secondary battery using the phosphate positive electrode material.
[0193] In Example 14, the first carbon source is VC, the second carbon source is PEG-2000, and the mass ratio of the two is controlled at 4:1, so that the compaction density of the phosphate positive electrode material is 1.88 g / cm 3 and BET specific surface area of 12.2 m 2 / g, the 0.1C first charge specific capacity of the secondary battery prepared by using the phosphate positive electrode material of Example 14 is 115mAh / g, the 0.1C first discharge specific capacity is 105mAh / g, the 0.1C first coulomb efficiency is 91.3%, the 1C first discharge specific capacity is 99mAh / g, and the 1C / 0.1C rate performance is 94.28%, and each performance is substantially lower than that of Examples 1, 9, and 12. This confirms that when the mass ratio of the two carbon sources is 4:1, using glucose as the main carbon source, a phosphate positive electrode material with higher compaction density and larger BET specific surface area can be obtained, which is conducive to obtaining a secondary battery with better electrochemical performance.
[0194] Compared with Example 1, the amount of carbon source used in Example 15 is reduced, the thickness of the carbon layer of the phosphate positive electrode material is reduced to 1.4nm, and the carbon content is reduced to 1.75%, resulting in a significant decrease in the compaction density and BET specific surface area of the phosphate positive electrode material, which in turn leads to a significant decrease in the 0.1C charge and discharge specific capacity, 0.1C first coulomb efficiency, 1C discharge specific capacity and 1C / 0.1C rate performance of the secondary battery prepared using the phosphate positive electrode material. The amount of carbon source used in Example 16 is increased, the thickness of the carbon layer of the phosphate positive electrode material is increased to 2.66nm, the carbon content is increased to 3.3%, the BET specific surface area of the phosphate positive electrode material is improved, but the compaction density of the phosphate positive electrode material is significantly reduced, resulting in the secondary battery prepared using the phosphate positive electrode material. Although the first coulomb efficiency and 1C / 0.1C rate performance are improved, the 0.1C charge and discharge specific capacity and 1C discharge specific capacity are significantly reduced. It can be seen that by controlling the total amount of the two carbon sources, a balance can be achieved between the compaction density and BET specific surface area of the phosphate positive electrode material and the charge and discharge capacity, first coulomb efficiency and rate performance of the secondary battery prepared using the phosphate positive electrode material, thereby obtaining a phosphate positive electrode material and secondary battery with better comprehensive performance.
[0195] In summary, the present application selects two carbon sources for carbon coating treatment, and by adjusting the composition and mass ratio of the carbon sources, a carbon layer with good density and high crystallinity can be formed on the surface of the inner core, giving the phosphate positive electrode material better electronic conductivity and structural stability, so that the compaction density and BET specific surface area of the phosphate positive electrode material are significantly improved, so that the secondary battery prepared using the phosphate positive electrode material has excellent performance in charge and discharge specific capacity, first coulomb efficiency and rate performance, thereby preparing a secondary battery with high energy density.
[0196] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A phosphate positive electrode material, characterized in that: comprising a core and a carbon layer covering the core; The inner core includes sodium vanadium fluorophosphate material; The compaction density of the phosphate positive electrode material is ≥1.78 g / cm 3 , BET specific surface area ≥9m 2 / g; The Raman spectrum of the phosphate positive electrode material has a D peak and a G peak, and the intensity ratio of the D peak to the G peak is (1.03-1.05):
1.
2. The phosphate positive electrode material according to claim 1, characterized in that One or more of the following conditions are met: (1) The mass ratio of the core to the carbon layer is 100:(1.75-3.3); (2) The thickness of the carbon layer is 1 nm to 3 nm; (3) The D50 particle size of the phosphate positive electrode material is 4 μm to 10 μm.
3. A method for preparing a phosphate positive electrode material, characterized in that: The following steps are involved: Mixing a vanadium source, a phosphorus source, a sodium source, a fluorine source, a carbon source and an aqueous phase, and performing a dispersion treatment to prepare a precursor slurry; Drying and calcining the precursor slurry to prepare the phosphate positive electrode material; The carbon source comprises a first carbon source and a second carbon source, the first carbon source and the second carbon source each independently comprise one or more of glucose, polyethylene glycol, sucrose and ascorbic acid, and the first carbon source and the second carbon source are different.
4. The method for preparing a phosphate positive electrode material according to claim 3, characterized in that: The first carbon source is glucose, and the second carbon source includes one or more of polyethylene glycol, sucrose and ascorbic acid.
5. The method for preparing a phosphate positive electrode material according to claim 4, characterized in that: The mass ratio of the first carbon source to the second carbon source is (1-6):
1.
6. The method for preparing a phosphate positive electrode material according to any one of claims 3 to 5, characterized in that: The molar ratio of the vanadium element in the vanadium source, the phosphorus element in the phosphorus source, the sodium element in the sodium source, the fluorine element in the fluorine source and the carbon element in the carbon source is 1: (0.8~1.2): (1.4~1.6): (1.4~1.6): (0.45~0.55).
7. The method for preparing a phosphate positive electrode material according to claim 6, characterized in that: One or more of the following conditions are met: (1) The vanadium source includes one or more of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, sodium metavanadate and sodium orthovanadate; (2) The phosphorus source includes one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate and sodium phosphate; (3) The sodium source includes one or more of sodium fluoride, sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate; (4) The fluoride source includes one or more of sodium fluoride and ammonium fluoride.
8. The method for preparing a phosphate positive electrode material according to claim 7, characterized in that: One or more of the following conditions are met: (1) The dispersion treatment includes one or more of ball milling and sand milling; (2) The solid content of the precursor slurry is 20% to 30%; (3) The D50 particle size of the precursor slurry is 0.4 μm to 0.6 μm; (4) The drying process comprises the following steps: spray drying the precursor slurry, wherein the inlet air temperature of the spray drying is 240°C to 260°C and the outlet air temperature is 90°C to 100°C, to obtain a dried material; (5) The calcination treatment comprises the following steps: heating to 550°C to 750°C in a protective atmosphere and keeping the temperature for 6h to 12h; (6) After the calcination treatment, the method further comprises the following steps: pulverizing, screening and iron removal of the calcined product to prepare a phosphate positive electrode material with a D50 particle size of 4 μm to 10 μm.
9. A positive electrode sheet, characterized in that: The invention comprises the phosphate positive electrode material according to claim 1 or 2, or comprises the phosphate positive electrode material prepared by the preparation method of the phosphate positive electrode material according to any one of claims 3 to 8.
10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.